Atopic dermatitis from adolescence to adulthood in the TOACS cohort: prevalence, persistence and comorbidities. Issue 7 (16th April 2015) - Mortz, C. G.; Andersen, K. E.; Dellgren, C.; Barington, T.; Bindslev‐Jensen, C.
Abstract Background While much is known about childhood atopic dermatitis, little is known about persistence of atopic dermatitis into adult life. We report, to our knowledge for the first time, the clinical course of atopic dermatitis in an unselected cohort of adolescents followed into adulthood. Methods The course of atopic dermatitis from adolescence to adulthood was studied prospectively in a cohort of unselected 8th‐grade schoolchildren established in 1995 and followed up in 2010 with questionnaire and clinical examination. Results The lifetime prevalence of atopic dermatitis was high (34.1%), and a considerable number of adults still suffered from atopic dermatitis evaluated both by questionnaire (17.1%) and clinical examination (10.0%). Persistent atopic dermatitis was found in 50% of those diagnosed in school age, and persistent atopic dermatitis was significantly associated with early onset, childhood allergic rhinitis and hand eczema. A close association was also found with allergic contact dermatitis and increased specific IgE to Malassezia furfur, but not with filaggrin gene defect. Conclusion Persistence of atopic dermatitis in adulthood is common and affects quality of life. Persistent atopic dermatitis is particularly prevalent in those with early onset, allergic rhinitis and hand eczema in childhood. It is important to recognizing atopic dermatitis as a common and disabling disease not only in children but also in adults.